Vegetation responses to the warming at the Younger Dryas-Holocene transition in the Hengduan Mountains, southwestern China - Wang, Xia; Yao, Yi-Feng; Wortley, Alexandra H.; Qiao, Hui-Jie; Blackmore, Stephen; Wang, Yu-Fei; Li, Cheng-Sen (Quaternary Science Reviews, 2018)
The Younger Dryas (YD) is one of the most abrupt climatic events in Earth's recent history. The warming at the end of the YD, in particular, is considered to be comparable to the global warming seen in the 21st century. However, the YD termination has received little attention, particularly in the Hengduan Mountains of Southwestern China, a low latitude temperate biodiversity hotspot. Here we present evidence for a rapid response in the diversity and composition of vegetation to the warming at the YD termination, based on a continuous, well-dated pollen sequence and loss-on-ignition data (12.9-9.2 cal. ka BP) from Haligu wetland in the Hengduan Mountains. Our data indicate that variations in plant diversity were correlated with relative humidity during this period, and suggest a distinct shift from Pinus-Abies-Picea forest to Pinus-dominated forest at the YD-Holocene transition, accompanied by an increase in coverage of generally temperate taxa such as Salix and Betula. This finding provides insights that may be of relevance to biodiversity conservation under future warming scenarios in similar mountain ecosystems worldwide. (C) 2018 Elsevier Ltd. All rights reserved.